Rolling regression CAPM on Zagreb stock exchange: Can investors profit from it? - Tihana Škrinjarić (Economic Review: Journal of Economics and Business, 2018)
This paper explores possibilities of using rolling regression CAPM on the Zagreb Stock Exchange in portfolio and risk management. Since original model has many flaws, one of them including the assumption of constant parameters in the model, extending the model with the assumption of changing parameters over time could lead to better results regarding portfolio risk and return. Furthermore, the rolling regression approach to CAPM estimation has not yet been observed on the Croatian and similar CEE markets, to the knowledge of the author. Weekly data on five sector indices from Zagreb Stock Exchange and the market index CROBEX with 91 day T-bill rates have been used for the period January 2012 - April 2018 in order to evaluate rolling regression CAPM on the Croatian market. Results from the analysis are used in simulating portfolio strategies in order to evaluate their performance regarding risk and return. Results indicate that such trading strategies could lead to better portfolio risk and return characteristics compared to the CROBEX benchmark, with the inclusion of transaction costs as well.
Keywords: G12; C22; G11; 330; asset pricing; rolling regression; risk hedging